POTENSI BIOPOLIMER DARI EKSTRAKSI NANOSELULOSA DAUN KAPAS SEBAGAI AGEN PENINGKATAN VISKOSITAS PADA INJEKSI POLIMER - Idham Khalid; Fitra Ayu Lestari; Muhammad Khairul Afdhol; Fiki Hidayat (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2020)
One of the methods used to optimize oil production is biopolymer injection. In this study, nanocellulose from cotton leaves was made into a biopolymer by combining the cotton leaf synthesis method with ascorbic acid, then sonified and hydrolyzed using ethanol. SEM and FTIR tests were carried out to see the size and chemical structure. The rheology of KLNC biopolymer was compared with the bipolymer from Xanthan Gum. The salinity and compatibility tests were carried out at various concentrations, as well as knowing the resistance of the biopolymer at reservoir temperature. The results of this study, the morphological shape of KLNC shows that the extraction process does not damage the surface structure. With the same concentration, KLNC biopolymer had a higher viscosity compared to Xanthan Gum biopolymer. KLNC biopolymer is more resistant to salinity and thermal than Xanthan Gum. So that KLNC Biopolymer has the potential to be further developed and researched.